Sodium-ion battery positive electrode material, preparation method and application

By introducing a multiphase structure of Li2MnO3 phase and O3 phase into the positive electrode material of sodium ion battery, combined with the P2 phase to form a superlattice structure, the problem of unstable structure of sodium ion battery positive electrode material under high voltage is solved, and the battery is improved Capacity retention and cycling performance.

CN119275281APending Publication Date: 2025-01-07CNGR ADVANCED MATERIAL CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411378188.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The structure of the existing sodium ion battery positive electrode materials is unstable at high voltage, resulting in low capacity retention and reduced electrochemical performance. In particular, O3 materials are prone to react with air to form impurities, and the sodium content of P2 materials is insufficient, which limits the circulation of the battery. performance.

Method used

Using a lithium-doped multiphase structure positive electrode material, including Li2MnO3 phase and O3 phase, the phase ratio of Li2MnO3 phase and the doped metal ratio is used to form a superlattice structure, and combined with the P2 phase, the structural stability and electrical properties of the material are improved. Chemical properties.

Benefits of technology

Through the formation of superlattice structure, the dissolution and lattice mismatch of the layered structure are suppressed, the capacity retention and cycling performance of sodium ion batteries are improved, and electrochemical performance optimization is achieved at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275281A_ABST
    Figure CN119275281A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery positive electrode material, a preparation method and application, the sodium-ion battery positive electrode material is a lithium-doped layered oxide, the sodium-ion battery positive electrode material is of a multi-phase structure, the multi-phase structure comprises a Li2MnO3 phase and an O3 phase, and the phase proportion [mu] Li2MnO3 of the Li2MnO3 phase is greater than or equal to 1wt% and less than or equal to 10wt%. According to the invention, Li is doped into the positive electrode material, so that a mixed-phase positive electrode material of an O3 phase and a Li2MnO3 phase is realized, the advantages of different phase structures are coupled, and guarantee is provided for the stability of the electrode structure of a high-capacity battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to sodium ion battery positive electrode materials, preparation methods and applications. Background Art

[0002] With the advancement of global high technology and the modernization of lifestyles, mobile devices and power grids have an increasing demand for energy storage. In this context, lithium-ion batteries have been widely used in the fields of power and energy storage, and currently account for more than 60% of the global rechargeable battery market. However, the scarcity, uneven distribution, high cost and increasing demand for lithium-ion batteries in the electric vehicle field have limited their application in large-scale energy storage systems. Sodium-ion battery raw materials, which have similar electrochemical properties to lithium-ion, are widely distributed, abundant in reserves and moderately priced, and have received increasing attention in recent years.

[0003] In secondary batteries, the performance of the positive electrode material is directly related to the overall performance of the battery. Among them, layered oxide positive electrode materials have shown great commercial potential and have received widespread attention due to their large theoretical specific capacity, high operating voltage, and easy large-scale production and preparation. According to the different stacking sequences of transition metals and sodium ions, layered oxide positive electrode materials can generally be divided into typical P2 structures and O3 structures. P2-type positive electrode materials have good air stability and cycle performance, but due to insufficient sodium content, the capacity is low; O3-type positive electrode materials have high sodium content, but are very easy to react with H2O and CO2 in the air to form impurities on the surface, resulting in decreased electrochemical performance. In addition, during the charge and discharge process of layered oxides under high voltage, Na + During the deintercalation process, Na + / Vacancy ordering and interlayer slip can lead to complex phase transitions. Frequent phase transitions can cause complex electrochemical behaviors, irreversible structural distortions, and huge volume changes, greatly reducing the cycle performance of the battery.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a sodium ion battery positive electrode material, a preparation method and an application thereof, taking into account both capacity and cycle performance.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a positive electrode material for a sodium ion battery, wherein the positive electrode material for a sodium ion battery is a layered oxide doped with lithium;

[0008] The sodium ion battery positive electrode material is a multiphase structure, and the multiphase structure includes a Li2MnO3 phase and an O3 phase, wherein the phase ratio of the Li2MnO3 phase is μ Li2MnO3Satisfy 1 wt% ≤ μ Li2MnO3 ≤ 10 wt%.

[0009] In an alternative embodiment, the XRD pattern of the positive electrode material of the sodium ion battery includes diffraction peaks at diffraction angles 2θ of 19° - 21°, 19° - 23° and 43° - 46°;

[0010] and / or, the XRD pattern of the positive electrode material of the sodium ion battery includes diffraction peaks at diffraction angles 2θ of 15° - 18° and 16° - 18°.

[0011] In an alternative embodiment, the multiphase structure of the positive electrode material of the sodium ion battery further includes a P2 phase.

[0012] In an alternative embodiment, the phase proportion μ of the P2 phase and the O3 phase of the positive electrode material of the sodium ion battery P2: μ O3 Satisfy 0 < μ P2: μ O3 ≤ 3.6;

[0013] Optionally, the phase proportion μ of the P2 phase and the O3 phase of the positive electrode material of the sodium ion battery P2: μ O3 Satisfy 0 < μ P2: μ O3 ≤ 1.

[0014] In an alternative embodiment, the XRD pattern of the positive electrode material of the sodium ion battery includes a diffraction peak at a diffraction angle 2θ of 14° - 17°.

[0015] In an alternative embodiment, the positive electrode material of the sodium ion battery satisfies at least one of the following conditions:

[0016] a. The chemical formula of the positive electrode material of the sodium ion battery is Na a Li b M 1-b O2, where 0.6 < a < 1, 0 < b < 0.5, and M is selected from at least one of Ni, Mn, Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe or Sr;

[0017] b. The chemical formula of the positive electrode material of the sodium ion battery is Na a (Ni x Mn y Li z M’ 1-x-y-z)O2; wherein 0.6<a<1, 0≤x<0.5, 0≤y<0.8, 0<z<0.5, and the value of a satisfies the valence balance, and x and y are not 0 at the same time; the M' is selected from at least one of Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, and Sr;

[0018] c. The phase ratio of the Li2MnO3 phase μ Li2MnO3 Satisfy 2wt%≦μ Li2MnO3 ≦8wt%.

[0019] In a second aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery according to any one of the aforementioned embodiments, comprising:

[0020] A mixture including a sodium source, a lithium source and a metal source is calcined in an oxygen-containing atmosphere, and then cooled, crushed and sieved in sequence to obtain the sodium ion battery positive electrode material.

[0021] In an optional embodiment, the method for preparing the positive electrode material of a sodium ion battery satisfies at least one of the following conditions:

[0022] A. Calcination includes first heating to a first temperature at a heating rate of 1°C / min-5°C / min, and keeping the temperature at the first temperature for 0.5h-10h; then heating to a second temperature at a heating rate of 1°C / min-5°C / min, and keeping the temperature at the second temperature for 0.5h-10h; then heating to 650°C-1000°C for calcination, and the calcination time is 10h-15h; optionally, the first temperature is 100°C-600°C, and the second temperature is higher than the first temperature;

[0023] B. The molar amount of lithium in the lithium source is more than 10% of the positive electrode material of the sodium ion battery; optionally, the molar amount of lithium in the lithium source is 10% to 50% of the positive electrode material of the sodium ion battery.

[0024] C. The metal source includes Ni and Mn elements; optionally, the metal source also includes M' element, and M' is selected from at least one of Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, and Sr.

[0025] In a third aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the aforementioned embodiment.

[0026] In a fourth aspect, the present invention provides an electrical device comprising the sodium ion battery described in the aforementioned embodiment.

[0027] The present invention has at least the following beneficial effects:

[0028] The sodium ion battery positive electrode material provided in the embodiment of the present invention is a multiphase positive electrode material including a Li2MnO3 phase and an O3 phase, and the phase ratio of the Li2MnO3 phase is μ Li2MnO3 Satisfy 1wt%≦μ Li2MnO3 ≦10wt%, Li2MnO3 phase belongs to the superlattice structure. Since the superlattice structure originates from the orderly arrangement of lithium ions entering the alkali metal layer in the layered structure, the dissolution of the layered structure and the lattice mismatch are inhibited, and the structural stability of the positive electrode material of the sodium ion battery is improved, thereby improving the capacity retention rate of the battery under high voltage; in addition, when the proportion of Li2MnO3 phase is low, the cycle retention rate of the battery is not significantly improved, and there is a capacity loss when the proportion is high. Therefore, when the proportion of Li2MnO3 phase is within an appropriate range, the comprehensive electrochemical performance of the sodium ion battery is the best.

[0029] The method for preparing the positive electrode material of a sodium ion battery provided in an embodiment of the present invention adopts a high-temperature solid-phase method, which is conducive to achieving the synthetic regulation of the ratio of layered P2, O3, and Li2MnO3 phases by changing conditions such as the doping metal ratio, sodium ratio, and lithium doping amount. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 is the XRD spectrum of the sodium ion positive electrode material in Example 1;

[0032] Figure 2 is the XRD spectrum of the sodium ion positive electrode material in Example 2;

[0033] Figure 3 is the XRD spectrum of the sodium ion positive electrode material in Example 3;

[0034] Figure 4 is the XRD pattern of the sodium ion positive electrode material in Example 4;

[0035] Figure 5 is the XRD pattern of the sodium ion positive electrode material in Example 5;

[0036] Figure 6 is the XRD spectrum of the sodium ion positive electrode material in Example 6;

[0037] Figure 7 The XRD pattern of the sodium ion positive electrode material in Comparative Example 1;

[0038] Figure 8 This is the XRD pattern of the sodium ion positive electrode material in Comparative Example 2;

[0039] Fig. 9 The XRD pattern of the sodium ion positive electrode material in Comparative Example 3;

[0040] Fig.10 This is the XRD pattern of the sodium ion positive electrode material in Comparative Example 4;

[0041] Fig.11 This is the XRD pattern of the sodium ion positive electrode material in Comparative Example 5;

[0042] Fig.12 This is the XRD pattern of the sodium ion positive electrode material in Comparative Example 6;

[0043] Fig.13 This is the standard XRD pattern of Li2MnO3. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0045] An embodiment of the present invention provides a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode material is a lithium-doped layered oxide;

[0046] The sodium ion battery positive electrode material is a multiphase structure, and the multiphase structure includes a Li2MnO3 phase and an O3 phase, wherein the phase ratio of the Li2MnO3 phase is μ Li2MnO3 Satisfy 1wt%≦μ Li2MnO3 ≦10wt%. The sodium ion battery positive electrode material provided in the embodiment of the present invention is a multiphase positive electrode material including a Li2MnO3 phase and an O3 phase, and the XRD pattern of the sodium ion battery positive electrode material is refined and calculated to obtain: the phase ratio of the Li2MnO3 phase μ Li2MnO3 Satisfy 1wt%≦μ Li2MnO3 ≦10wt%,μ Li2MnO3 It can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or satisfy 1wt%≦μ Li2MnO3 Any value of ≦10wt%, preferably 2wt%-8wt%.

[0047] The Li2MnO3 phase belongs to a superlattice structure. Since the superlattice structure originates from the orderly arrangement of lithium ions entering the alkali metal layer in the layered structure, it inhibits the dissolution of the layered structure and the lattice mismatch, and improves the structural stability of the positive electrode material of the sodium ion battery, thereby improving the capacity retention rate of the battery at high voltage; in addition, when the proportion of the Li2MnO3 phase is low, the cycle retention rate of the battery is not significantly improved, and there is a capacity loss when the proportion is high. Therefore, when the proportion of the Li2MnO3 phase is within an appropriate range, the comprehensive electrochemical performance of the sodium ion battery is best.

[0048] In an optional embodiment, in the sodium ion battery positive electrode material:

[0049] The dominant crystal plane of the P2 phase layered metal oxide is the (002) crystal plane or the (103) crystal plane;

[0050] and / or, the dominant crystal plane of the O3 phase layered metal oxide is a (003) crystal plane or a (104) crystal plane;

[0051] And / or, the dominant crystal planes of the Li2MnO3 phase are (020), (111) and (133) planes.

[0052] In an optional embodiment, the XRD spectrum of the sodium ion battery positive electrode material includes diffraction peaks at diffraction angles 2θ of 19°-21°, 19°-23° and 43°-46°, which are the diffraction peaks of the Li2MnO3 phase (020) crystal plane, (111) crystal plane and (133) crystal plane, respectively.

[0053] In an optional embodiment, the XRD spectrum of the sodium ion battery positive electrode material includes diffraction peaks at diffraction angles 2θ of 15°-18° and 16°-18°, which are the diffraction peaks of the (003) crystal plane of O3 phase sodium layered metal oxide and O3 phase lithium layered metal oxide, respectively.

[0054] In an optional embodiment, the multi-phase structure of the sodium ion battery positive electrode material also includes a P2 phase.

[0055] P2-type materials contain more sodium ion vacancies and relatively low sodium ion diffusion barriers, and usually exhibit good kinetic performance. However, the low sodium content limits the available capacity, and violent phase changes often occur after deep sodiation, resulting in poor structural stability. O3-type materials, on the other hand, have a higher sodium content, can provide a higher initial capacity, and are more promising for practical applications. However, the phase change process is often complex and the rate performance is poor. In this embodiment, the O3 phase, P2 phase, and Li2MnO3 phase are all layered structures and are intercalated with each other, which can effectively suppress the volume change during charge and discharge. When the positive electrode material is a three-phase composite layered oxide, it combines the advantages of different phase structures, providing guarantee for the electrode structure stability of high-capacity batteries. In an alternative embodiment, the phase proportion μ P2: μ O3 satisfies 0 < μ P2: μ O3 ≤ 3.6;

[0056] Optionally, the phase proportion μ P2: μ O3 of the P2 phase and the O3 phase of the sodium ion battery positive electrode material P2: μ O3 satisfies 0 < μ

[0057] Specifically, by performing refined calculation on the XRD pattern of the sodium ion battery positive electrode material, it is obtained that μ P2: μ O3 can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.6 or any value that satisfies 0 < μ P2: μ O3 ≤ 3.6. If the phase proportion of the P2-phase layered metal oxide is too high, it is not conducive to the improvement of the capacity of the positive electrode material.

[0058] In an alternative embodiment, the XRD pattern of the sodium ion battery positive electrode material includes a diffraction peak at a diffraction angle 2θ of 14° - 17°, which is the diffraction peak of the (002) crystal plane of the P2-phase layered metal oxide.

[0059] In an alternative embodiment, the sodium ion battery positive electrode material satisfies at least one of the following conditions:

[0060] a. The chemical formula of the sodium ion battery positive electrode material is Na a Li b M 1-b O2, where 0.6 < a < 1, 0 < b < 0.5, and M is selected from at least one of Ni, Mn, Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, or Sr.

[0061] b. The chemical formula of the sodium ion battery positive electrode material is Na a (Ni x Mn y Li z M' 1-x-y-z )O2; wherein, 0.6<a<1, 0≤x<0.5, 0≤y<0.8, 0<z<0.5, and the value of a satisfies the valence balance, and x and y are not 0 at the same time; and the M' is selected from at least one of Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, and Sr.

[0062] In the embodiment of the present application, the doping element M' can be selected according to the requirements for the performance of the positive electrode material, and is preferably Cu, Ca, Mg, Zn, Sr, Ti, Zr, and Al.

[0063] c. Phase ratio of Li2MnO3 phase μ Li2MnO3 Satisfy 2wt%≦μ Li2MnO3 ≦8wt%,μ Li2MnO3 The positive electrode material within this range has better performance.

[0064] An embodiment of the present invention further provides a method for preparing the positive electrode material for a sodium ion battery according to any one of the aforementioned embodiments, comprising:

[0065] A mixture including a sodium source, a lithium source and a metal source is calcined in an oxygen-containing atmosphere, and then cooled, crushed and sieved in sequence to obtain the sodium ion battery positive electrode material.

[0066] Specifically, in this embodiment, the synthetic regulation of the ratio of O3 phase layered metal oxide to Li2MnO3 phase is achieved mainly by changing the conditions such as the doping metal ratio, sodium ratio and lithium doping amount, or the synthetic regulation of the ratio of O3 phase layered metal oxide, P2 phase layered metal oxide and Li2MnO3 phase is achieved.

[0067] In an optional embodiment, the method for preparing the positive electrode material of a sodium ion battery satisfies at least one of the following conditions:

[0068] A. Calcination includes first heating to a first temperature at a heating rate of 1°C / min-5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1°C / min-5°C / min; keeping at the first temperature for 0.5h-10h, specifically 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or any value between 0.5h-10h; and then heating to a second temperature at a heating rate of 1°C / min-5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min or any value between 1°C / min-5°C / min. The temperature is kept at a second temperature for 0.5 h to 10 h, specifically 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value between 0.5 h and 10 h; the temperature is raised to 650 ° C to 1000 ° C for calcination, specifically 650 ° C, 700 ° C, 750 ° C, 800 ° C, 850 ° C, 900 ° C, 950 ° C, 1000 ° C or any value between 650 ° C and 1000 ° C; the calcination time is 10 h to 15 h, specifically 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or any value between 10 h and 15 h. Optionally, the first temperature is 100°C-600°C, specifically 100°C, 200°C, 300°C, 400°C, 500°C, 600°C or any value between 100°C-600°C; the second temperature is higher than the first temperature.

[0069] The calcination process can affect the formation of the crystalline phase, and changes in calcination conditions may lead to changes in the composition of the positive electrode material, which in turn may lead to changes in capacity or stability.

[0070] B. The molar amount of lithium in the lithium source is more than 10% of the positive electrode material of the sodium ion battery; Optionally, the molar amount of lithium in the lithium source is 10% to 50% of the positive electrode material of the sodium ion battery, specifically 10%, 20%, 30%, 40%, 50% or any value of 10% to 50% or more than 50%. During the synthesis of the positive electrode material of the sodium ion battery, most of the lithium preferentially enters the transition metal layer to maintain the layered structure, and acts as a "pillar" in the form of Li-Li dimers to stabilize the layered structure and inhibit the formation of high-voltage crystalline oxygen vacancies. Further increasing the amount of lithium doping, a small part of lithium will occupy the sodium position of the alkali metal layer to produce a Li-O3 phase, and the orderly arrangement between the lithium ions entering the alkali metal and the layered structure forms a layered Li2MnO3 phase with high stability. This superlattice structure is conducive to inhibiting the dissolution and lattice mismatch of the layered structure to improve the structural stability of the positive electrode material, thereby improving the capacity retention rate of the positive electrode material under high voltage, so the lithium content needs to be within a reasonable range.

[0071] C. The metal source includes Ni and Mn elements; optionally, the metal source also includes M' element, M' is selected from at least one of Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, and Sr. In the mixture, the sodium source can be selected from sodium carbonate, sodium hydroxide, and sodium nitrate, the lithium source can be selected from lithium carbonate, lithium hydroxide, and lithium nitrate, and the metal source can exist in the form of at least one of hydroxide, oxide, carbonate, organic acid salt, and chloride. The sodium source, lithium source, and metal source can be ball-milled to uniformly mix the components in the mixture, and the amount of each component can be calculated according to the chemical formula of the target positive electrode material.

[0072] An embodiment of the present invention further provides a sodium ion battery, comprising the sodium ion battery positive electrode material described in the aforementioned embodiment.

[0073] An embodiment of the present invention further provides an electrical device, comprising the sodium ion battery described in the aforementioned embodiment.

[0074] The features and performance of the present invention are further described in detail below in conjunction with the examples. The test methods for testing the products involved in the following examples and comparative examples are described as follows:

[0075] Embodiment 1:

[0076] This embodiment provides a sodium ion battery positive electrode material Na 0.87 Ni 0.18 Fe 0.19 Mn 0.52 Mg 0.01 Li 0.10 O2, the specific preparation method is as follows:

[0077] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, Fe2O3 and MnO2, and then add them to the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace, and keep the temperature at 350℃ for 1h under air atmosphere, continue to heat to 500℃ and keep the temperature for 3h, and finally calcine at 960℃ for 12h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.87 Ni 0.18 Fe 0.19 Mn 0.52 Mg 0.01 Li 0.10 O2 sodium-ion battery cathode materials.

[0078] Embodiment 2:

[0079] This embodiment provides a sodium ion battery positive electrode material Na 0.804 Ni 0.20 Mn 0.312 Ti 0.35 Cu 0.01 Li 0.128 O2, the specific preparation method is as follows:

[0080] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, TiO2, MnO2 and CuO, and then add them to the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 350℃ for 1h, continue to heat to 500℃ and keep the temperature for 3h, and finally calcine at 960℃ for 12h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.804 Ni 0.20 Mn 0.312 Ti 0.35 Cu 0.01 Li 0.128 O2 sodium-ion battery cathode materials.

[0081] Embodiment 3:

[0082] This embodiment provides a sodium ion battery positive electrode material Na 0.83 Ni 0.18 Mn 0.30 Ti 0.36 Cu 0.01 Li 0.15 O2, the specific preparation method is as follows:

[0083] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, TiO2 and MnO2, and then add them to the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 350℃ for 1h, continue to heat to 500℃ and keep the temperature for 3h, and finally calcine at 960℃ for 12h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.83 Ni 0.18 Mn 0.30 Ti 0.36 Cu 0.01 Li 0.15 O2 sodium-ion battery cathode materials.

[0084] Embodiment 4:

[0085] This embodiment provides a sodium ion battery positive electrode material Na 0.78 Ni 0.19 Fe 0.06 Mn 0.63 Mg 0.02 Li 0.10 O2, the specific preparation method is as follows:

[0086] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, Fe2O3, MnO2 and MgO, and then add them to the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 350℃ for 1h, continue to heat to 500℃ and keep the temperature for 3h, and finally calcine at 960℃ for 12h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.78 Ni 0.19 Fe 0.06 Mn 0.63 Mg 0.02 Li 0.10 O2 sodium-ion battery cathode materials.

[0087] Embodiment 5:

[0088] This embodiment provides a sodium ion battery positive electrode material Na 0.81 Ni 0.19 Fe 0.03 Mn 0.64 Mg 0.01 Zn 0.01 Li 0.12 O2, the specific preparation method is as follows:

[0089] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, Fe2O3, MnO2, ZnO and MgO, and then add them to the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 350℃ for 1h, continue to heat to 500℃ and keep the temperature for 3h, and finally calcine at 960℃ for 12h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.81 Ni 0.19 Fe 0.03 Mn 0.64 Mg 0.01 Zn 0.01 Li 0.12 O2 sodium-ion battery cathode materials.

[0090] Embodiment 6:

[0091] This embodiment provides a sodium ion battery positive electrode material Na 0.85 Ni 0.17 Fe 0.01 Mn 0.65 Mg 0.01 Li 0.16 O2, the specific preparation method is as follows:

[0092] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, Fe2O3, MgO and MnO2, and then add them to the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 350℃ for 1h, continue to heat to 500℃ and keep the temperature for 3h, and finally calcine at 960℃ for 12h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.85 Ni 0.17 Fe 0.01 Mn 0.65 Mg 0.01 Li 0.16 O2 sodium-ion battery cathode materials.

[0093] Comparative Example 1:

[0094] This comparative example provides a sodium ion battery positive electrode material Na 0.90 Ni 0.22 Fe 0.16 Mn 0.47 Mg 0.10 Zn 0.05 O2, the specific preparation method is as follows:

[0095] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, Fe2O3, MnO2, MgO and ZnO respectively, and then add them into the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, and heat them at a constant temperature of 1℃ / min at 980℃ for 15h, then cool them with the furnace, crush them with a universal crusher, and sieve them with 400 mesh to obtain the molecular formula of Na 0.90 Ni 0.22 Fe 0.16 Mn 0.47 Mg 0.10 Zn 0.05 O2 sodium-ion battery cathode materials.

[0096] Comparative Example 2:

[0097] This comparative example provides a sodium ion battery positive electrode material Na 0.875 Ni 0.20 Fe 0.195 Mn 0.48 Mg 0.055 Zn 0.04 Li 0.0 3O2, the specific preparation method is as follows:

[0098] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, Fe2O3, MnO2, MgO and ZnO respectively, and then add them into the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, and heat them at a constant temperature of 1℃ / min at 980℃ for 15h, then cool them with the furnace, crush them with a universal crusher, and sieve them with 400 mesh to obtain the molecular formula of Na 0.875 Ni 0.20 Fe 0.195 Mn 0.48 Mg 0.055 Zn 0.04 Li 0.03 O2 sodium-ion battery cathode materials.

[0099] Comparative Example 3:

[0100] This comparative example provides a sodium ion battery positive electrode material Na 0.875 Ni 0.20 Fe 0.195 Mn 0.49 Mg 0.045 Zn 0.02 Li 0.0 5O2, the specific preparation method is as follows:

[0101] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, Fe2O3, MnO2, MgO and ZnO respectively, and then add them into the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, and heat them at a constant temperature of 1℃ / min at 980℃ for 15h, then cool them with the furnace, crush them with a universal crusher, and sieve them with 400 mesh to obtain the molecular formula of Na 0.875 Ni 0.20 Fe 0.195 Mn 0.49 Mg 0.045 Zn 0.02 Li 0.05 O2 sodium-ion battery cathode materials.

[0102] Comparative Example 4:

[0103] This comparative example provides a sodium ion battery positive electrode material Na 0.80 Ni 0.22 Mn 0.29 Ti 0.31 Cu 0.18 O2, the specific preparation method is as follows:

[0104] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, TiO2, MnO2 and CuO, and then add them into the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 550℃ for 6h, heat to 930℃ and calcine at a constant temperature for 10h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.80 Ni 0.22 Mn 0.29 Ti 0.31 Cu 0.18 O2 sodium-ion battery cathode materials.

[0105] Comparative Example 5:

[0106] This comparative example provides a sodium ion battery positive electrode material Na 0.78 Ni 0.23 Mn 0.35 Ti 0.29 Cu 0.07 Li 0.06 O2, the specific preparation method is as follows:

[0107] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, TiO2, MnO2 and CuO, and then add them into the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 550℃ for 6h, heat to 930℃ and calcine at a constant temperature for 10h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.78 Ni 0.23 Mn 0.35 Ti 0.29 Cu 0.07 Li 0.0 6O2 is a positive electrode material for sodium-ion batteries.

[0108] Comparative Example 6:

[0109] This comparative example provides a sodium ion battery positive electrode material Na 0.70 Ni 0.20 Mn 0.42 Ti0.275 Cu 0.015 Li 0.09 O2, the specific preparation method is as follows:

[0110] According to the chemical formula, weigh the corresponding weight of Na2CO3, Li2CO3, NiO, TiO2, MnO2 and CuO, and then add them into the mixer at a speed of 2000r / min and mix for 3min. Put the mixed materials into the muffle furnace under air atmosphere, keep the temperature at 550℃ for 6h, heat to 930℃ and calcine at a constant temperature for 10h, then cool with the furnace, crush with a universal crusher, and sieve with 400 mesh to obtain the molecular formula of Na 0.70 Ni 0.20 Mn 0.42 Ti 0.275 Cu 0.015 Li 0.09 O2 sodium-ion battery cathode materials.

[0111] The XRD patterns of the positive electrode materials obtained in each embodiment and comparative example are as follows: Figure 1-12 As shown, the standard XRD pattern of Li2MnO3 is as follows Fig.13 As shown (XRD was measured by X-ray diffractometer, determined according to the reference standard GA / T 2079-2023, the crystal structure of each sample was tested using Rigaku SmartLab 9kW X-ray diffractometer (XRD, Cu Kα), with a scanning range of 5-80° and a scanning rate of 8° / min). The XRD results of each embodiment and comparative example are shown in Table 1.

[0112] Table 1

[0113]

[0114]

[0115] The positive electrode materials obtained in each embodiment and comparative example are stirred evenly with the conductive agent and the binder in NMP solvent, and then coated on aluminum foil. After that, they are baked, rolled, and sliced ​​to form positive electrode sheets. Finally, the positive electrode sheets are assembled with the diaphragm, the sodium sheet, and the gasket to form a CR2032 sodium ion button battery. The electrolyte is sodium perchlorate containing 1 mol / L, the solvent volume ratio EC (ethylene carbonate): PC (propylene carbonate) = 1:1, and the solvent also includes FEC (fluoroethylene carbonate) with a mass fraction of 5%. The sodium sheet negative electrode is tested for the electrical properties of the sodium ion button battery. The test conditions are: the voltage range is 2.0-4.2V and 2.0-4.3V, and the test temperature is 25±1°C. The specific test conditions for the button battery are: charge to 4.2 / 4.3V at 0.1C, discharge to 2.0V at 0.1C, cycle for 2 weeks, then charge to 4.2 / 4.3V at 0.2C, discharge to 2.0V at 0.2C, cycle for 2 weeks, finally charge to 4.2 / 4.3V at 1C, discharge to 2.0V at 1C, cycle for 50 weeks at 1C, and the test results are shown in Table 2.

[0116] Table 2

[0117]

[0118] From Table 1 and Table 2, we can see that:

[0119] The sodium ion positive electrode material in Examples 1-6 includes a Li2MnO3 phase and an O3 phase, and the phase ratio of the Li2MnO3 phase is μ Li2MnO3 Satisfy 1wt%≦μ Li2MnO3 ≦10wt%, so that the material not only has good electrochemical capacity, but also has excellent stability and electrochemical cycle performance.

[0120] From Comparative Examples 1, 2 and 3, it can be seen that although Comparative Examples 2 and 3 are doped with lithium, the amount of lithium doping is relatively small. + It preferentially enters the transition metal layer to form the Li-O3 phase and cannot form the Li2MnO3 phase, which is ultimately accompanied by capacity decay and limited improvement in retention rate.

[0121] It can be seen from Examples 4-6 that by doping 10%, 12% and 16% lithium respectively in a layered oxide system mainly composed of nickel, iron and manganese, a three-phase composite structure of O3, P2 and Li2MnO3 phases appears in the positive electrode material of the sodium ion battery, and the XRD diffraction angles are at 20.25°-20.42°, 21.98°-22.01°, and 43.78°-45.40°. When the Li2MnO3 phase accounts for 5.57%, the capacity is almost not reduced, and the capacity retention rate under high voltage is also improved, and the comprehensive electrochemical performance is the best.

[0122] In summary, based on the different system positive electrode materials of the present invention, controllable regulation of the composite symbiosis of various layered structures can be achieved. A certain amount of Li2MnO3 phase can be formed by controlling lithium doping. The Li2MnO3 phase belongs to a superlattice structure. The superlattice structure originates from the lithium ions entering the alkali metal layer and the orderly arrangement in the layered structure, which inhibits the dissolution and lattice mismatch of the layered structure, and improves the high-voltage structural stability of the positive electrode material while ensuring excellent capacity, and has excellent cycle performance.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery is a layered oxide doped with lithium; The sodium ion battery positive electrode material is a multiphase structure, and the multiphase structure includes a Li2MnO3 phase and an O3 phase, wherein the phase ratio of the Li2MnO3 phase is μ Li2MnO3 Satisfy 1wt%≦μ Li2MnO3 ≦10wt%.

2. The sodium ion battery positive electrode material according to claim 1, characterized in that The XRD spectrum of the sodium ion battery positive electrode material includes diffraction peaks at diffraction angles 2θ of 19°-21°, 19°-23° and 43°-46°; And / or, the XRD spectrum of the sodium ion battery positive electrode material includes diffraction peaks at diffraction angles 2θ of 15°-18° and 16°-18°.

3. The sodium ion battery positive electrode material according to claim 1, characterized in that The multiphase structure of the sodium ion battery positive electrode material also includes a P2 phase.

4. The sodium ion battery positive electrode material according to claim 3, characterized in that The phase ratio μ of the P2 phase and the O3 phase of the sodium ion battery positive electrode material P2: μ O3 Satisfy 0<μ P2: μ O3 ≦3.6; Optionally, the phase ratio μ of the P2 phase to the O3 phase of the sodium ion battery positive electrode material is P2: μ O3 Satisfy 0<μ P2: μ O3 ≦1.

5. The sodium ion battery positive electrode material according to claim 1, characterized in that The XRD spectrum of the sodium ion battery positive electrode material includes a diffraction peak at a diffraction angle 2θ of 14°-17°.

6. The sodium ion battery positive electrode material according to claim 1, characterized in that The sodium ion battery positive electrode material meets at least one of the following conditions: a. The chemical formula of the positive electrode material of the sodium ion battery is Na a Li b M 1-b O2, where 0.6 < a < 1, 0 < b < 0.5, and M is selected from at least one of Ni, Mn, Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, or Sr; b. The chemical formula of the sodium ion battery positive electrode material is Na a (Ni x Mn y Li z M' 1-x-y-z )O2; wherein 0.6<a<1, 0≤x<0.5, 0≤y<0.8, 0<z<0.5, and the value of a satisfies the valence balance, and x and y are not 0 at the same time; the M' is selected from at least one of Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, and Sr; c. The phase ratio of the Li2MnO3 phase μ Li2MnO3 Satisfy 2wt%≦μ Li2MnO3 ≦8wt%.

7. A method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 6, characterized in that: include: A mixture including a sodium source, a lithium source and a metal source is calcined in an oxygen-containing atmosphere, and then cooled, crushed and sieved in sequence to obtain the sodium ion battery positive electrode material.

8. The method for preparing a positive electrode material for a sodium ion battery according to claim 7, characterized in that: The method for preparing the positive electrode material for a sodium ion battery satisfies at least one of the following conditions: A. The calcination includes first heating to a first temperature at a heating rate of 1°C / min-5°C / min, and keeping the temperature at the first temperature for 0.5h-10h; then heating to a second temperature at a heating rate of 1°C / min-5°C / min, and keeping the temperature at the second temperature for 0.5h-10h; then heating to 650°C-1000°C for calcination, and the calcination time is 10h-15h; optionally, the first temperature is 100°C-600°C, and the second temperature is higher than the first temperature; B. The molar amount of lithium in the lithium source is more than 10% of the positive electrode material of the sodium ion battery; optionally, the molar amount of lithium in the lithium source is 10% to 50% of the positive electrode material of the sodium ion battery; C. The metal source includes Ni and Mn elements; optionally, the metal source also includes M' element, and M' is selected from at least one of Ca, Mg, K, W, Zr, Cr, Mo, Nb, Sb, Ta, Ho, Bi, Cu, Sn, Zn, Ce, La, Y, Ti, Co, Al, Fe, and Sr.

9. A sodium ion battery, characterized in that: The sodium ion battery positive electrode material comprises any one of claims 1 to 6.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.

Citation Information

Cited By

  • P2 / O3 double-phase composite material, preparation method and application thereof, and sodium ion battery

    CN119764431A